Personalized Massive Open Online Course for Childhood Cancer Survivors: Behind the Scenes - Berger, Claire; Casagranda, Léonie; Sudour-Bonnange, Hélène; Massoubre, Catherine; Dalle, Jean-Hugues; Teinturier, Cecile; Martin-Beuzart, Sylvie; Guillot, Pascale; Lanlo, Virginie; Schneider, Muriele; Dal Molin, Bernard; Dal Molin, Michèle; Mounier, Olivier; Garcin, Arnauld; Fresneau, Brice; Clavel, Jacqueline; Demoor-Goldschmidt, Charlotte (Applied Clinical Informatics, 2021)
Background Today, in France, it is estimated that 1 in 850 people aged between 20 and 45 years has been treated for childhood cancer, which equals 40,000 to 50,000 people. As late effects of the cancer and its treatment affect a large number of childhood cancer survivors (CCS) and only 30% of them benefit from an efficient long-term follow-up care for prevention, early detection, and treatment of late effects, health education of CCS represents a challenge of public health.Objectives Massive open online courses (MOOCs) are a recent innovative addition to the online learning landscape. This entertaining and practical tool could easily allow a deployment at a national level and make reliable information available for all the CCS in the country, wherever they live.Methods The MOOC team brings together a large range of specialists involved in the long-term follow-up care, but also associations of CCS, video producers, a communication consultant, a pedagogical designer, a cartoonist and a musician. We have designed three modules addressing transversal issues (lifestyle, importance of psychological support, risks of fertility problems) and eight modules covering organ-specific problems. Detailed data on childhood cancer treatments received were used to allocate the specific modules to each participant.Results This paper presents the design of the MOOC entitled “Childhood Cancer, Living Well, After,” and how its feasibility and its impact on CCS knowledge will be measured. The MOOC about long-term follow-up after childhood cancer, divided into 11 modules, involved 130 participants in its process, and resulted in a 170-minute film. The feasibility study included 98 CCS (31 males vs. 67 females; p < 0.0001).Conclusion Such personalized, free, and online courses with an online forum and a possible psychologist consultation based on unique characteristics and needs of each survivor population could improve adherence to long-term follow-up without alarming them unnecessarily.
Keywords: survivors of childhood cancer; health education; information technology; massive open online course